Richard Rolle’s Psalter Rendition: The Work of a Language Purist? - Lis, Kinga (Studia Anglica Posnaniensia, 2015)
Richard Rolle’s Psalter rendition, as any of the medieval English Psalter translations, is thickly enveloped in a set of assertions, originating in the nineteenth century, whose validity has been accepted unquestioned. It is the purpose of the present paper to investigate one such claim concerning the vocabulary selection, according to which Rolle’s rendition would employ almost exclusively lexical items of native origin, except for the instances where no proper item with native etymology presents itself in a particular context and Rolle is forced to use a Latin-derived word. The assertion generates at least two problematic issues. Firstly, it identifies Rolle’s translation as most exceptional in relation to the remaining 14th-century English Psalter translations: the Wycliffite Bibles and the Middle English Glossed Prose Psalter of which the former are asserted to be overtly influenced by the Latin text they render and the latter deeply indebted both syntactically and, more importantly, lexically to a ‘French source’. Secondly, it ascribes Richard Rolle the ideas nowadays covered by the term linguistic purism. Therefore, it seems necessary to analyse the lexical layer of the text in search of evidence, or lack thereof, which sets Rolle’s translation lexically apart from other renditions and sheds some light on the issue of Rolle’s supposed linguistic purism. Such a study is conducted on the basis of the nominal layer of the first fifty Psalms of the four relevant texts analysed in relation to their common Latin source text as only the juxtaposition of all of these enables one to (dis)prove the claim cited above. To provide a wider context from which to view them, the findings will be presented in relation to an overview of the contemporary theory of translation and set against a broadly sketched linguistic map of contemporary England.